The investigation of approach run in terms of age, gender, bio-motor and technical components on vaulting table - Örs, B. S.; Bayraktar, I.; Bagci, E.; Altunsoy, M.; Pekel, H. A. (Science of Gymnastics Journal, 2021)
Vault is one of the main apparatuses for both female and male gymnasts in artistic gymnastics (AG). The optimal vaulting technique depends on many variables, such as the approaching run. Gymnastics is one of the early specialization sports as it is necessary to start training at an early age. For this reason, the aim of the current study was to investigate the relationship among age, biomotor and technical components in relation to the approach run velocity and other variables in AG. Furthermore, similarities and differences between genders were researched. Twenty female and twelve male gymnasts took part in the study. Speed, agility, explosive power, run-up velocity were measured. Additionally, Reactive Strength Index (RSI) and Peak High Velocity distances (PHV_Distance) were calculated. Kinematic parameters during the handspring vault were calculated by a two-dimensional video analysis. A statistical comparison between genders was performed by the Mann Whitney U test. The relationships between parameters were given by Spearman correlation coefficients (r). Anaerobic power, 0-20 m speed, 20 m speed velocity, and the hand contact time were significantly different between genders (p<0.05). The approach run significantly correlated with the chronological age (r=0.66; p=0.002 for female and r=0.96; p<0.001 for male gymnasts), PHV_Distance (r=0.69; p=0.001 for female and r=0.97; p<0.001 for male gymnasts) and the biological age (r=0.69; p=0.001 for female and r=0.97; p<0.001 for male gymnasts). As the approach run velocity increases, vaulting performance is affected positively. While speed tests significantly correlated with the approach run in male gymnasts, there was no correleation for females. In addition, trainers should keep in mind that the relationship between bio-motor development and biological age of gymnasts is important in training programs.